Peranan Teknologi dalam Meningkatkan Kualitas Pengajaran Bahasa di SMA Negeri 1 Janapria - Wildan Wildan (Educatio, 2022)
This study aims to determine the role of technology in improving the quality of language teaching at SMAN 1 Jaanapria. This type of research is quantitative and qualitative research. The research method used combines qualitative and quantitative methods (mix methods). The data obtained from this study were from interviews and observations and data obtained from questionnaires/questionnaires. There are two elements studied in the data analysis: the element of student learning motivation and the element of the role of technology in language learning. From the discussion, it can be concluded that the student's learning motivation in class averages 65.5%, meaning that students at SMAN 1 Janapria on average often pay attention to teachers in class. Besides that, students also desire to solve problems and discuss them with others. Other students for the learning process. While the role of language learning technology is an average of 56.3%, meaning that students and educators, especially teachers, sometimes use technology in the language learning process. Students think technology is needed to support the language teaching and learning process in the classroom.